Rapid Assessment of Avoidable Blindness and Willingness to Pay for Cataract Surgery in Tribal Region of Surat District of Gujarat State, India. (4th March 2021) - Chariwala, Rohan A.; Shah, Shaheen P.; Patel, Daksha; Chaudhari, Sheetal P.; Gajiwala, Uday R.
ABSTRACT: Aim: To estimate prevalence and causes of avoidable blindness among people ≥50 years and to assess willingness to pay (WTP) for cataract surgery in tribal region of south Gujarat, India. Methods: A cross-sectional population based survey was conducted with 44 randomly selected clusters each having 50 people aged ≥50 years selected by probability proportional to size of sampling. Adults identified with cataract causing visual loss (<6/18) in any eye were interviewed to assess their WTP for surgery. Results: Total of 2137 examined out of 2200 people enumerated (response rate 97.1%). The prevalence of blindness (Presenting Visual Acuity (PVA)<3/60 in better eye) was 2.23% (95% CI: 2.95%–1.51%). Cataract was main cause of blindness (67.3%) followed by corneal scarring (8.2%). Major barrier to cataract surgery cited by bilaterally blind people was lack of escort to the surgical facility (34.3%). Cataract surgical coverage (CSC) was 84.9% (eyes) and 92% (persons). Of the 492 people interviewed to assess WTP for their surgery, only 36.4% people were willing to pay. Conclusion: The tribal population has a high poverty profile in India. Within this group, cataract remains the main treatable cause of blindness despite a high CSC. Assessment of barriers suggested that a well-coordinated outreach programme with free transport facilities to the surgical facility is required along with strategies to improve accessibility and prioritising cataract blind in the community. One-third of people were willing to pay for their surgeries implying that cross subsidization or tier system could be feasible for eye care programme sustainability.